Palący oddechem wąż („serpens flatu adurens”) św. Hieronima - Morta, Krzysztof (Vox Patrum, 2023)
The article is about a mention of serpens flatu adurens - ‘a serpent burning with its breath’ (Deut 8:14) found in St. Jerome’s translation of the Old Testament. The snake is listed among other venomous animals that threatened the Israelites during their journey through the desert. The article intends to answer – basing on the ancient historicity and literature – what kind of actual snake is behind this extraordinary description. In his translation St. Jerome mentions different snake species known in the Graeco-Roman world, as equivalents to their Hebrew names. As is turns out, Jerome took the discussed in the article term from Symmachus. And Symmachus, in turn, drew on rabbinic commentary and made a mistake of mistranslating the Hebrew text. The mistake was, however, acceptable for Jerome in relation to the basilisk. In the ancients’ belief this serpent – along with its deadly abilities – had a power of burning everything around. St. Jerome introduced the name of the basilisk to the Bible seven times (in Septuagint the snake appears only twice). The discussed case would be the 8th mention of the basilisk in Jerome’s translation of the Bible.